Jump rope training - Lee, Buddy 1958- (Human Kinetics, 2010)
United States wrestling champion Buddy Lee presents an athletic training program that utilizes jump roping to help people improve their speed, agility, balance, strength, power, and endurance, with exercises and drills including warm-ups, cool-downs, fitness, and sport-specific training